SIKAP MAHASISWA FAKULTAS ILMU KEOLAHRAGAAN UNIVERSITAS NEGERI YOGYAKARTA TERHADAP KECELAKAAN LALU LINTAS - Yustinus Sukarmin (LPMPP Universitas Negeri Yogyakarta, 2009)
This study aimed to investigate the attitudes of the students in the Faculty of Sports Sciences, the Yogyakarta State University, towards attempts to prevent traffic accidents. This study was a descriptive study on attitudes. The research population consisted of the students from both regular and non-regular programs in all the study programs, namely PJKR, PKO, Ikora, and PGSD study programs. The sample consisted of 340 students out of 2,447 students, selected by using the proportional sampling technique. The data were collected by using the Likert scale in which each item had four options. The data were analyzed by using the descriptive quantitative technique employing the percentage. The results of the study showed that the students attitudes towards attempts to prevent traffic accidents were good enough (79.58%). This indicated that the students had a great concern in the victims of traffic accidents and had a high motivation to be involved in attempts to prevent and deal with traffic accidents. Keywords: attitudes, traffic accidents